2010
DOI: 10.1111/j.1439-0531.2009.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Cryopreservation Techniques: Higher Survival and Implantation Rate of Frozen–Thawed Mouse Pronuclear Embryos in the Presence of Beta‐Mercaptoethanol in Post‐Thaw Culture

Abstract: The objective of this study was to investigate the effects of beta-mercaptoethanol (β-ME) on post-thaw embryo developmental competence and implantation rate of mouse pronuclear (PN) embryos that were cryopreserved after slow freezing, solid surface vitrification (SSV) or open-pulled straw (OPS) vitrification methods. Mouse PN embryos were cryopreserved by using slow freezing, SSV and OPS methods. After cryopreservation, freeze-thawed PN embryos were cultured up to blastocyst stage in a defined medium supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Similarly, the embryos were placed in biopsy medium for 30 min to loosen the bonds between the blastomeres to prevent compacting. In the study presented here, the rates of embryo development with the aspiration technique used in the eight-cell stage and the development rates in the study by Krzyminska et al (13) were found to be similar.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Similarly, the embryos were placed in biopsy medium for 30 min to loosen the bonds between the blastomeres to prevent compacting. In the study presented here, the rates of embryo development with the aspiration technique used in the eight-cell stage and the development rates in the study by Krzyminska et al (13) were found to be similar.…”
Section: Discussionsupporting
confidence: 69%
“…Bagis et al (13) obtained embryos from CB6F1 mice and cultured them in SAGE medium until the blastocyst stage. Their result for mean total cell number was 58.9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…unknown damages caused by somatic cell nuclear transfer can reduce the number of healthy embryos [18], while cotransfer compensates for this by increasing the total number of healthy embryos to trigger and maintain pregnancy. Likewise, in the case of cryopreservation, some reports have described damage to freeze-thawed embryos [1,24], implying that cotransfer of carrier embryos could assist the implantation and subsequent development of freeze-thawed embryos.…”
Section: Discussionmentioning
confidence: 99%
“…As it is valid for most of the rather new technologies, case reports on vitrification of zygotes were published in series (Jelinkova et al, 2002;Selman and El-Danasouri, 2002;Kumasako et al 2005). Even under aggravated conditions, such as the presence of an artificial gap in the zona pellucida after polar body biopsy, unsuspicious development to blastocyst stage and live births were reported for mice and humans (Isachenko et al, 2005a, Naether et al, 2008Macas et al, 2008Macas et al, , 2011Bagis et al, 2010;Vanderzvalmen et al 2012). Interestingly, re-vitrification of previously vitrified and warmed 2PN-stages turned out to be a feasible option Kumasako et al, 2009) although not always resulting in pregnancy and live birth (Hashimoto et al, 2007).…”
Section: Zygotementioning
confidence: 99%